TREATMENT OF POLYNEUROPATHY WITH BERLITHION (Ta'limning zamonaviy transformatsiyasi, 2024)
A comparison study of efficacy and tolerability of the drug berlition 300 oral and berliton 300 U and vitamin B1 has been conducted in 56 patients with alcohol polyneuropathy (15 female, 41 male, mean age 42.6 years). The key mechanisms of berlition action are increasing of endoneural blood flow, strengthening of antioxidant system functioning and reduction of "oxidative stress" intensity; improvement of glucose consumption and restoring of nerve energetic balance as well as intensification of nerve growth factor releasing and nerve growth acceleration after its experiment cutting or squeezing. Usage of berlition in the cohort studied was accompanied by a positive dynamics of both subjective and objective clinical symptoms. Comparing to vitamin B1, the drug was significantly more effective by clinical and electrophysiological indices. Berlition therapy is tolerable and safe. The results of the study confirm an assumption of berlition efficacy in alcohol polyneuropathy and allow to recommend the drug for a wide clinical application.